Jambeiro: propagação, aspectos morfológicos e caracterização qualitativa - Nacata, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The cultivation of Syzygium can be a source of diversification of the agricultural activity, since its physical and qualitative characteristics are attractive for the consumers. Having as origin the Asian Continent, the malay, rose and water apple present characteristics that allow their commercialization in the national territory. However, the lack of studies on the three species mentioned is remarkable. The present work aimed to provide more information about the three species of Syzygium, studying seed propagation and cutting, morphological description of the germination process and pollen grains, pollen and stigmatic viability, biometric characterization of fruits, leaves and seeds, besides qualitative characterization of its fruits. The results show that the rose apple presents a higher rate of germination and polyembryony. Temperatures influence the percentage of germination, polyembryony and Germination Speedy Index (GSI). For the malay and rose apple. The seeds present green color cotyledons, hygienic germination with primary root of brown coloration and whitish secondary, short and filiform. For cutting, for optimization of the process and reduction of expenses, the use of indolbutyric acid (AIB) becomes dispensable and the maintenance of the whole leaves on the cuttings promotes an increase in the length and average number of roots. The malay jamb has a fruit mass between 35.06 and 56.20 (g); Seed between 11.55 and 16.05 (g); Length and width of fruits between 4.93 to 5.91 (cm) and 3.98 to 4.77 (cm); Seed width from 2.86 to 3.44 (cm). The water apple presents maximum percentage of pulp, and parameters equal to red as length, leaf width and petiole length and leaf area. The rose apple is the smallest among those studied. There are differences in pollen morphology for the three species studied, it is observed that S. jambos is the largest species in the polar and equatorial diameter, S. aqueum has a larger polar diameter, in relation to S. malaccense, and the last one mentioned with smaller polar and equatorial diameter when compared with the other species. The pollen feasibility test allows to conclude that rose apple and water apple that bloom in the same period can compete for the same pollinating agents depending on the pollen availability schedules and stigma receptivity. For the qualitative analysis of the fruits it is verified that there are differences between the analyzed species, with the fruits of the malay and water apple present: increase of mass, decrease of firmness, greater chromaticity, increase of soluble solids, decrease of titratable acidity, increase of pH, increase of ascorbic acid and respiration as they reached a higher degree of maturation. The fruits of the malay apple have a four times lower content of ascorbic acid and their respiration is altered according to the degree of maturation of the fruit when compared to the water apple, which does not change.

O cultivo de jambeiro pode ser fonte de diversificação da atividade agrícola, visto que suas características físicas e qualitativas são atrativas para os consumidores. Tendo como origem o Continente Asiático, os jambeiros vermelho, amarelo e rosa apresentam características que viabilizam sua comercialização no território nacional. No entanto, é notável a carência de estudos sobre as três espécies citadas. O presente trabalho objetivou, desta forma, trazer maiores informações sobre as três espécies de jambeiro, estudando a propagação por sementes e por estaquia, descrição morfológica do processo germinativo e dos grãos de pólen, verificando viabilidade polínica e estigmática, caracterização biométrica de frutos, folhas e sementes, além de caracterização qualitativa de seus frutos. Os resultados evidenciam que o jambeiro amarelo apresenta maior taxa de germinação e poliembrionia. As temperaturas influenciam na porcentagem de germinação, poliembrionia e IVG. para os jambeiros vermelho e amarelo. As sementes apresentam cotilédones de coloração verde, germinação hipógea com raiz primária de coloração marrom e secundárias esbranquiçadas, curtas e filiformes. Para a estaquia, visando otimização do processo e redução de gastos, a utilização de ácido indolbutírico (AIB) se torna dispensável e a manutenção das folhas inteiras nas estacas promove aumento do comprimento e número médio de raízes. O jambeiro vermelho tem massa de fruto entre 35,06 a 56,20(g); semente entre 11,55 a 16,05 (g); comprimento e largura dos frutos entre 4,93 a 5,91(cm) e 3,98 a 4,77(cm); largura das sementes entre 2,86 a 3,44(cm). O jambeiro rosa apresenta máxima porcentagem de polpa, e parâmetros iguais ao vermelho quanto comprimento, largura da folha e comprimento do pecíolo e área foliar. O Jambeiro amarelo é o menor entre os estudados. Existem diferenças na morfologia polínica para as três espécies estudadas, observa-se que o S. jambos é a espécie de maior tamanho no diâmetro polar e equatorial, S. aqueum apresenta maior diâmetro polar, em relação ao S. malaccense, e a última citada com menor diâmetro polar e equatorial quando comparada com as outras espécies. O teste de viabilidade do pólen permite concluir que as espécies de jambeiros (amarelo e rosa) que florescem no mesmo período podem competir pelos mesmos agentes polinizadores em função dos horários de disponibilidade de pólen e receptividade do estigma. Para a análise qualitativa dos frutos verifica-se que existem diferenças entre as espécies analisadas, sendo que os frutos dos jambeiros vermelho e rosa apresentam: aumento da massa, diminuição da firmeza, maior cromaticidade, aumento de sólidos solúveis, diminuição da acidez titulável, aumento do pH, aumento do ácido ascórbico e da respiração conforme atingem maior grau de maturação. Os frutos do jambeiro vermelho têm um teor quatro vezes mais baixo de ácido ascórbico e sua respiração é alterada conforme o grau de maturação do fruto, quando comparado ao jambeiro rosa, que não se altera.
Syzygium: propagation, morphological aspects and qualitative characterization
Keywords: Syzygium; Cutting Process; Germination; Pollen; Estaquia; Germinação; Pólen